1974
DOI: 10.1172/jci107757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemorrhage on Regional Blood Flow Distribution in Dogs and Primates

Abstract: A B S T R A C T The effects of hemorrhage on arterial pressure, blood flows, and resistances in the coronary, mesenteric, renal, and iliac beds of healthy, conscious dogs and intact, tranquilized baboons were studied. Mild nonhypotensive hemorrhage (14±2 ml/kg) increased heart rate and mesenteric and iliac resistances slightly but significantly, and decreased renal resistance (-13± 2%). Moderate hypotensive hemorrhage, 26±2 ml/kg, reduced mean arterial pressure (-23±2 mm Hg) and blood flows to the mesenteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
2
2

Year Published

1976
1976
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(82 citation statements)
references
References 39 publications
(76 reference statements)
6
72
2
2
Order By: Relevance
“…Similarly, in the present study HH was found to increase renal medullary prostaglandin concentration. These findings, in addition to the above mentioned ressults of Vatner (15) and Data et al (4), prompted further investigation of the importance of prostaglandin synthesis during hemorrhage. Inhibition of prostaglandin synthesis with either of two chemically dissimilar agents (indomethacin and RO 20-5720) was found to have a profound effect oIn the renal ischemic response to HH.…”
Section: Resultsmentioning
confidence: 73%
“…Similarly, in the present study HH was found to increase renal medullary prostaglandin concentration. These findings, in addition to the above mentioned ressults of Vatner (15) and Data et al (4), prompted further investigation of the importance of prostaglandin synthesis during hemorrhage. Inhibition of prostaglandin synthesis with either of two chemically dissimilar agents (indomethacin and RO 20-5720) was found to have a profound effect oIn the renal ischemic response to HH.…”
Section: Resultsmentioning
confidence: 73%
“…In contrast, no significant reduction in renal blood flow occurred. We have previously reported that during hemorrhagic hypotension to 72 mm Hg in pregnant rabbits, renal blood flow was 16±3.2% of CO (5), and renal vasodilatation (12) and preservation of renal blood flow during hemorrhagic hypotension have been reported in dogs and primates (13). These studies would indicate that uterine blood flow is not maintained as well as renal blood flow with severe hypotension induced by ganglionic blockade.…”
Section: Discussionmentioning
confidence: 92%
“…The protection afforded by the prophylactic administration of furosemide in several models of ischemic acute tubular necrosis has never been clearly explained (35) but evokes an intriguing parallel to the prevention of mTAL anoxic damage during isolated perfusion by decreasing 02 demand by cells. Indeed, the redistribution of cortical flow in favor ofthe medulla, an early event in hypotension (36), and the profound disproportionate fall in GFR in acute renal failure might be viewed, at least in part, as a regulatory mechanism developed to protect the mTAL from the dangerous and precarious equilibrium between 02 demand and supply within the outer medulla of the kidney.…”
Section: Discussionmentioning
confidence: 99%